Pengaruh Beban Kerja, Stres Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Bagian Produksi PT. INKA Multi Solusi Madiun - Milafatul Qoyyimah; Tegoeh Hari Abrianto; Siti Chamidah (Universitas Muhammadiyah Ponorogo, 2020)
This research aims to determine the effect of Workload, Work Stress and Work Environment on Employee Performance in the Production Section of PT. INKA Multi Solusi Madiun and the second to find out the most dominant variable among the variables of workload, work stress and work environment on the performance of the employees of PT. INKA Multi Madiun Solutions. The population in this study were all employees of PT. INKA Multi Madiun Solutions and the sample used in this study were 304 employees using Simple Random Sampling. The data analysis method used is Multiple Linear Regression with the help of SPSS. The results of this study indicate that: (1) Workload has a negative effect (-1,052) and has no significant effect on the performance of the employees of PT. INKA Multi Solusi Madiun, (2) Work stres has a negative effect (-5.120) and is significant on the performance of the employes of PT. INKA Multi Solusi Madiun, (3) The work environment has a positive effect (10,873) and is significant on the performance of the employes of PT. INKA Multi Madiun Solutions, and (4) Workload, Work Stress and Work Environment have a positive effect on (49,969) and are significant together on the performance of employees of PT. INKA Multi Madiun Solutions.